2013
DOI: 10.1097/jwh.0b013e31828c1ab3
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Chronic Back Pain and Stress Urinary Incontinence

Abstract: Objective The objective of this study was to investigate the association between chronic back pain and urinary incontinence in women. Study Design This study was a cross-sectional, observational study. Background There are numerous factors associated with the development of back pain, yet little consideration has been given to the pelvic floor musculature and dysfunction of this musculature which may also cause urinary incontinence. Currently, limited research exists evaluating the relationship between bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
1
25
0
1
Order By: Relevance
“…When stratified by age groups (younger, middle‐aged, and older people) or sex the results were similar. There were inconsistent results when examining the type of urinary incontinence (stress, urge, mixed) and its association with low back pain . When testing for a linear relationship between low back pain severity and frequency/degree of urinary incontinence some populations demonstrated this and others did not .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When stratified by age groups (younger, middle‐aged, and older people) or sex the results were similar. There were inconsistent results when examining the type of urinary incontinence (stress, urge, mixed) and its association with low back pain . When testing for a linear relationship between low back pain severity and frequency/degree of urinary incontinence some populations demonstrated this and others did not .…”
Section: Resultsmentioning
confidence: 99%
“…11,12 One study considered storage and voiding symptoms, 11 and four studies evaluated specific subtypes of incontinence. 5,6,11,12 The studies all demonstrated that there was a statistically significant association between the diagnosis of urinary incontinence or urinary symptoms and low back pain, with adjusted odds ratios varying from 1.1 to 3.1. When stratified by age groups (younger, middle-aged, and older people) 10,13,18 or sex 9 the results were similar.…”
Section: Epidemiological Assessment Of Urinary Symptoms and Low Bacmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing body of evidence demonstrating links between SUI and back pain [14][15][16]. In a study of 38,050 healthy Australian women [14], self-report data was used to establish associations between back pain, pelvic floor weakness and disorders of respiration, while considering confounding factors of BMI and physical activity.…”
Section: Introductionmentioning
confidence: 99%